Metallized film for secondary battery positive electrode and manufacturing method thereof

The surface shape and crystal growth of the aluminum metal film are controlled by vacuum evaporation method, and the problems of rising contact resistance of the conductive film layer on the surface of the resin and insufficient filmization strength of the metal foil are solved, achieving efficient conductive performance and free transfer.

CN119563247APending Publication Date: 2025-03-04TORAY KP FILMS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380052854.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-12
Filing Date
2023-06-27
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

When a conductive film layer is formed on the resin surface, the contact resistance is prone to rise, and the filmization of the metal foil leads to insufficient strength, making it difficult to carry without breakage.

Method used

The surface shape of the vapor deposition film is controlled by vacuum evaporation method to form an aluminum metal film, the ratio of the X-ray diffraction peak intensity of the 200 surfaces to the 111 surfaces is 1.0 or more, the surface resistance is 0.15Ω/□ or less, the surface roughness of the resin film is 0.6 nm or more, and the surface roughness of the aluminum metal film is 2.3 nm or more and 10.0 nm or less.

Benefits of technology

It is realized that the contact resistance is not increased when the conductive film layer is formed on the resin surface and the conveyance is carried without breakage, thereby improving the strength and conductive properties of the metallized film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119563247A_ABST
    Figure CN119563247A_ABST
Patent Text Reader

Abstract

The present invention addresses the problem of obtaining: a metallized film in which contact resistance does not increase even if a conductive film layer is formed on a resin surface, and which can be transported without breakage; and a method for manufacturing the metallized film. The problem can be solved by a metallized film for a secondary battery positive electrode in which an aluminum metal film is formed on at least one surface of a resin film, and the ratio I [200] / I [111] of the X-ray diffraction peak intensity I [200] of the 200 plane to the X-ray diffraction peak intensity I [111] of the 111 plane of aluminum in the metal film is 1.0 or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a metallized film for a secondary battery positive electrode and a method for producing the same. Background Art

[0002] In recent years, due to the miniaturization of electrical and electronic equipment and environmental issues, secondary batteries, capacitors and other storage batteries for gasoline-powered vehicles (hybrid vehicles, electric vehicles) have been required to be smaller and lighter, while also requiring high output density that can be charged and discharged instantly with large currents.

[0003] In order to improve the weight energy density, the battery mounted on the vehicle generally has the following structure: the positive electrode and the negative electrode are formed in a sheet shape, and the sheet-shaped positive electrode and the negative electrode are stored in a casing in a wound or stacked state via a separator also formed in a sheet shape. The sheet-shaped electrode plate is formed in a structure in which a mixture layer containing an active material is formed on the surface of a metal foil serving as a current collector.

[0004] In addition, as one of the methods for obtaining high output density, there is a method of reducing the resistance of various materials constituting the battery (internal resistance of the battery). In the battery, aluminum foil is often used for the collector, but the collector made of ordinary aluminum foil has an oxide film, and it is believed that the internal resistance increases due to the oxide film formed on the aluminum surface. When the internal resistance increases, the voltage drops when charging and discharging with a large current, resulting in a decrease in the output of the battery. Generally, a natural oxide film of an insulator with a thickness of 5 to 10 nm is usually formed on aluminum, but as for the aluminum surface, it has the characteristic of maintaining good conductivity. As a reason for this, there are the following statements: the current flows from the defective part of the oxide film; in the field of quantum mechanics, based on the tunneling phenomenon in which electrons break free from the region that they cannot normally cross in energy with a certain probability, if the electron conductor sandwiches the electrical insulator and approaches about 10 nm or less, a tunneling effect of good electron conduction is generated; etc. Although it has not yet been clarified, it can be considered that the aluminum oxide film itself has a strong influence on the internal resistance.

[0005] As a method for suppressing the contact resistance between the electrode and the active material due to the increase in internal resistance caused by the oxide film, there is a method of making the surface of the metal foil used for the electrode uneven (for example, Patent Document 1). Although it is not clear whether the number of defects increases by roughening the aluminum surface or the tunnel effect is easily manifested by forming a large number of protrusions, it is effective as a method for reducing contact resistance.

[0006] As a method for improving high output density while miniaturization and lightness, with the purpose of improving volume energy density and improving weight energy density, the filmization of electrode substrates is being promoted. However, if the metal foil used for the electrode to be processed is simply filmized, the problem of insufficient strength will occur. In addition, if the surface unevenness of the thin-filmed metal foil is increased for the purpose of reducing contact resistance, it will further become the reason for the reduction of the strength of the metal foil, which is undesirable. Therefore, as a new material to replace metal, it is proposed to make the material having a conductive film layer such as a metal provided on the surface of a biaxially stretched polyester film with excellent mechanical properties and heat-resistant dimensional stability have a collector function, and use it as an electrode substrate (for example, patent document 2).

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2008-160053

[0010] Patent Document 2: Japanese Patent Application Laid-Open No. 10-40919 Summary of the invention

[0011] Problems to be solved by the invention

[0012] However, in the case of a structure in which a conductive thin film layer such as metal is provided on the surface of a resin film such as a polyester film, the total resistance value increases by the amount of thinning of the metal thickness compared to the metal foil used in the past. Moreover, even if the metal surface is roughened for the purpose of reducing the contact resistance of the aluminum metal surface, since the conductive thin film layer such as metal provided on the surface of the resin film is usually a vapor-deposited metal film formed by vacuum evaporation method and is a thin film metal, it is still difficult to roughen it by etching or the like. If the surface of the polyester film itself is roughened, it will become easy to break, and the transportation in the manufacturing process will become difficult.

[0013] In view of the above circumstances, an object of the present invention is to provide a metallized film which does not increase contact resistance even when a conductive thin film layer is formed on a resin surface and which can be transported without being broken.

[0014] Means for solving problems

[0015] The inventors of the present application have conducted intensive studies in view of the above-mentioned problems and have found that a metallized thin film having a low contact resistance and a method for producing the same can be obtained by controlling the surface shape of a vapor-deposited film using a vacuum vapor deposition method.

[0016] That is, the present invention relates to:

[0017] A metallized film for a secondary battery positive electrode, wherein an aluminum metal film is formed on at least one surface of a resin film, wherein the ratio of the peak intensity I

[200] of the X-ray diffraction of the aluminum of the metal film at the 200 plane to the peak intensity I

[111] of the X-ray diffraction of the aluminum at the 111 plane is 1

[200] / I

[111] or more.

[0018] The metallized film for the positive electrode of the secondary battery, wherein the surface resistance of the metal film is 0.15Ω / □ or less,

[0019] The metallized film for the positive electrode of the secondary battery, wherein the surface roughness Ra of the resin film is 0.6 nm or more and 2.0 nm or less,

[0020] The metallized thin film for a secondary battery positive electrode has a surface roughness Ra of the metal film of not less than 2.3 nm and not more than 10.0 nm.

[0021] In addition, the present invention relates to:

[0022] A method for producing a metallized film for a positive electrode of a secondary battery, the method comprising: a vacuum evaporation method in which argon gas is introduced when heating aluminum of a evaporation source by at least one selected from the group consisting of resistance heating, induction heating, and electron beam to vaporize aluminum, and a step of vaporizing the vaporized aluminum on a resin film to form a film;

[0023] The method for producing the metallized film for a secondary battery positive electrode includes forming an aluminum film on the resin film by sputtering, and then forming a film by evaporating the vaporized aluminum without exposing the film to the atmosphere.

[0024] Effects of the Invention

[0025] According to the present invention, it is possible to obtain a metallized film which does not increase contact resistance even when a conductive thin film layer is formed on a resin surface and which can be transported without breaking, and a method for producing the same. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] [ Figure 1 ] is a schematic cross-sectional view of the metallized film of the present invention.

[0027] [ Figure 2 ] is a schematic cross-sectional view of the metallized film of the present invention.

[0028] [ Figure 3 ] is a schematic cross-sectional view of the metallized film of the present invention.

[0029] [ Figure 4] is an electron microscope (SEM) photograph of the surface of an aluminum metal film (film thickness 1.48 μm) when the grains are grown large and densely using an induction heating evaporation source using a carbon crucible.

[0030] [ Figure 5 ] is a SEM photograph of the surface of an aluminum metal film (film thickness: 0.53 μm) when a carbon crucible-based induction heating evaporation source is used to grow large and dense grains.

[0031] [ Figure 6 ] is a SEM photograph of the surface of an aluminum metal film (film thickness: 1.12 μm) grown by a boat heating method in which aluminum metal wires are continuously supplied to a resistance-heated boat.

[0032] [ Figure 7 ] is a SEM photograph of a cross section of an aluminum metal film (film thickness 1.48 μm) when a carbon crucible-based induction heating evaporation source is used to grow large and dense grains; (with Figure 3 Same but different viewing direction). DETAILED DESCRIPTION

[0033] The present invention is described in detail below.

[0034] <Metalized film>

[0035] The metallized film 4 of the present invention has an aluminum metal film 3 ( Figure 1 , Figure 2 , Figure 3 ).

[0036] <Aluminum Metal Film>

[0037] The aluminum metal film 3 in the present invention is an aggregate of aluminum metals formed by laminating one or more layers containing aluminum as the main component. The main component means that the main component accounts for more than 80 atomic % when the entire layer is taken as 100 atomic %.

[0038] The thickness of the aluminum metal film 3 in the present invention is preferably 0.7 μm to 3.0 μm, and more preferably 1.0 μm to 2.5 μm.

[0039] In electrode applications, the lower the resistance, the better. In terms of surface resistance, the surface resistance of the metal film is preferably less than 0.15Ω / □, and more preferably less than 0.05Ω / □. On the other hand, in order to increase the energy density, thin filming is required, so simply making the metal film thicker is not desirable. Considering the resistance of the electrode, the thickness of the aluminum metal film is preferably greater than 0.7μm. If it is greater than 1.0μm, it becomes a lower resistance, which can reduce the increase in internal resistance. On the other hand, from the purpose of increasing the volume energy density, it is necessary to further promote the thin filming of the electrode substrate, preferably less than 3.0μm, and more preferably less than 2.5μm.

[0040] The aluminum metal film 3 in the present invention has a feature that the contact resistance can be reduced by controlling the crystal growth of the metal film so that the surface irregularities become larger during film formation by vacuum deposition.

[0041] On a 10mm thick NR sponge rubber, the aluminum metal film 3 of the metallized film 4 is placed in an upward manner, and two copper plates of 25mm×25mm size that have been gold-plated are separated by an interval of 1mm and a weight of 500g is placed on each copper plate. The resistance value between the two copper plates is used as the value of the contact resistance. At this time, in order to reduce the internal resistance increase, the contact resistance value is preferably less than 15mΩ, and more preferably less than 10mΩ. The contact resistance value here is the value of the contact resistance of the two electrode areas including 25mm×25mm and the film resistance (surface resistance) between the two electrodes. Therefore, the ratio of the contact resistance value to the surface resistance value [contact resistance value] / [surface resistance value] can show a value with a small influence of the surface resistance, and the ratio of the surface resistance value [contact resistance value] / [surface resistance value] is preferably less than 0.35, and more preferably less than 0.25.

[0042] As a feature of the surface of the aluminum metal film 3 that controls the crystal growth of the metal film and reduces the contact resistance, the surface roughness Ra of the aluminum metal film 3 that is not in contact with the resin film 1 is preferably 2.3 nm or more and 10.0 nm or less, and more preferably 5.0 nm or more and 10.0 nm or less. When the aluminum surface is sufficiently roughened and a certain degree of size is ensured in terms of the height of the convex and concave portions, there is a tendency for the contact resistance to become lower, and the larger the surface roughness Ra, the more preferred it is. However, if the surface roughness Ra is too large, the thin aluminum metal film 3 becomes the cause of the metal film breakage during transportation and bending, so it is preferably less than 10.0 nm.

[0043] As a feature of the surface of the aluminum metal film 3 for controlling the crystal growth of the metal film and reducing the contact resistance, the ratio of the peak intensity I

[200] of the X-ray diffraction of the aluminum 200 plane of the aluminum metal film 3 to the peak intensity I

[111] of the X-ray diffraction of the 111 plane is preferably 1.0 or more and 10 or less. I

[200] / I

[111] is further preferably 2.0 or more. The larger the intensity ratio I

[200] / I

[111] , the more densely the crystal orientation of the aluminum metal film 3 is aligned, so that the film resistance (surface resistance) becomes smaller and the contact resistance of the contact surface is also reduced.

[0044] Since aluminum is a cubic crystal system, when aluminum is in powder form, the crystal orientation is random, so the peak intensity of X-ray diffraction at the 111 plane is the largest, and the intensity ratio I

[200] / I

[111] is less than 1.0. The metal particles of aluminum metallized thin films produced by conventional vacuum evaporation methods are columnar crystal films with large gaps, and the peak intensity of X-ray diffraction at the 111 plane is the largest, and the intensity ratio I

[200] / I

[111] is less than 1.0.

[0045] On the other hand, rolled aluminum foil becomes dense through the rolling process, and the crystal orientation is aligned, so the peak intensity I

[111] of the X-ray diffraction of the oblique 111 plane becomes weaker, and the intensity ratio I

[200] / I

[111] becomes greater than 1.0. By increasing the surface temperature of the substrate (referring to the resin film. The resin film is sometimes referred to as the substrate below) during evaporation, the columnar crystals become larger and denser, so that the crystals are aligned in the 200 plane direction, and the intensity ratio I

[200] / I

[111] becomes greater than 1.0. However, in the case where the substrate is a resin film, if the substrate temperature is increased, it will melt and break. Therefore, if it is not time-consuming to make it, the substrate temperature cannot be increased, and the metal particles of the aluminum metal film produced by vacuum evaporation become a columnar crystal film with large gaps, and the intensity ratio I

[200] / I

[111] becomes less than 1.0.

[0046] In the present invention, even if the substrate is a resin film, by increasing the surface temperature of the substrate and introducing argon gas, the columnar crystals of the aluminum metal film are grown large and dense, and the crystal grains are enlarged, thereby successfully forming appropriate concavities and convexities on the surface of the aluminum metal film. By increasing the heat generated by the evaporation source while forcibly cooling the resin film from the back, the temperature near the surface of the resin film exposed to the evaporation source is increased, and the columnar crystals can be made large and dense.

[0047] In the case of a general aluminum vacuum deposition method, a boat heating method is used to continuously supply aluminum metal wires to a resistance-heated boat, but when an aluminum metal film is formed in this way, the intensity ratio I

[200] / I

[111] becomes less than 1.0. Therefore, in order to make the substrate surface temperature rise easily, it is preferred to make the calorific value of the evaporation source as large as possible and form the film in a short time. By using an evaporation source with a large calorific value, an induction heating method using a carbon crucible or a method of heating using an electron beam, the calorific value of the evaporation source becomes large, and the grains can be grown large and dense. However, in such a case, the resin film will melt due to heat, so it is preferred to force the resin film to be cooled from the back to a temperature close to the point where it does not melt, so that the columnar crystals of the aluminum metal film grow large and dense. Furthermore, by introducing argon gas during evaporation, it is possible to further form concave and convex on the surface of the aluminum metal film.

[0048] Figure 4 and Figure 5 This is a SEM photograph of the surface of an aluminum metal film when large and dense grains are grown on the surface of a resin film (here, a polyethylene terephthalate (PET) film) with a surface roughness Ra of 1.6 nm using an evaporation source using an induction heating method with a carbon crucible that generates a large amount of heat. Figure 4 This is a surface SEM photo of a 1.48μm thick aluminum metal film. Figure 5 This is a surface SEM photo of a 0.53 μm thick aluminum metal film. Figure 4 and Figure 5 It can be judged that by increasing the size of the crystal grains, appropriate irregularities can be formed on the surface of the aluminum metal film. Figure 4 8.3nm in Figure 5 The thickness of the nanostructured carbon fiber is 2.7nm.

[0049] Figure 7 yes Figure 4 From the cross-sectional SEM photo of the aluminum metal film, it can be judged that the aluminum metal film is a columnar crystal, and the convex and concave portion of the aluminum metal film surface is equivalent to a columnar crystal. Therefore, it is inferred that the larger the size of the convex and concave portion of the aluminum metal film surface, the larger and denser the columnar crystal. Figure 4 and Figure 5 In the case of Figure 4 In the case of , the growth of columnar crystals is larger.

[0050] on the other hand, Figure 6 This is a SEM photograph of the surface of an aluminum metal film grown by a boat heating method in which aluminum metal wires are continuously supplied to a general resistance heating boat. Figure 6 This is a SEM photo of the surface of an aluminum metal film with a thickness of 1.12 μm. The surface roughness Ra is 2.2 nm. Figure 6 No obvious projections and depressions were observed on the surface of the aluminum metal film, so it is presumed that the columnar crystals did not grow significantly and did not grow densely.

[0051] In order to make the grains grow and form a dense metal film, it is necessary to expose it to the evaporation source as a heat source for a certain period of time. As a result, the evaporation time needs to be extended. The thickness of the aluminum metal film is preferably greater than 0.7μm, and more preferably greater than 1.0μm.

[0052] <Method for producing aluminum metal film>

[0053] As a film forming method of the aluminum metal film 3, for the purpose of making a thin electrode, a vacuum evaporation method that can form a metal film on a thin resin film without using an adhesive is preferred. Vacuum evaporation methods include induction heating evaporation method, resistance heating evaporation method, laser beam evaporation method, electron beam evaporation method, etc., but among them, electron beam evaporation method, laser beam evaporation method, and induction heating evaporation method with a large calorific value of the evaporation source are preferably used. As for the calorific value of the evaporation source, it is necessary to increase it until the grains of the aluminum metal film 3 are large and densely formed, and the surface temperature of the substrate needs to be sufficiently high, but due to the difficulty of actual measurement, it is necessary to confirm the physical properties of the aluminum metal film 3 after evaporation to determine whether it is sufficient heat.

[0054] When the calorific value of the evaporation source is increased to the necessary heat, the temperature of the resin film rises and there is a possibility of melting in the management of the cooling function of the usual vacuum evaporation method. Therefore, in order to prevent the temperature from rising excessively during evaporation, it is necessary to manage the cooling function in a manner that can evenly cool the film while performing evaporation. Specifically, it is necessary to use a cooling mechanism having a metal plate or metal roller that is fully cooled by a refrigerant to evenly cool from the back of the evaporation surface. In order to cool evenly, it is necessary to fit the resin film and the cooling mechanism tightly without generating a gap.

[0055] For example, if there is a scratch on the metal roller of the cooling mechanism, the scratched part becomes a gap, and the resin film cannot be cooled and melted at the scratched part. For example, if foreign matter enters the resin film and the metal roller of the cooling mechanism, the resin film cannot be cooled and melted due to the foreign matter. When the calorific value of the evaporation source rises to the necessary heat, the scratches and foreign matter mixed into the metal roller allowed in the usual vacuum evaporation method become a problem, so the management of the scratches and foreign matter mixed into the metal roller needs to be more stringent. By increasing the heat generation of these evaporation sources and strengthening the management of the cooling function, the grains of the aluminum metal film 3 can be grown larger and densely formed, so that the internal resistance including the contact resistance is reduced. In particular, in the case of electron beam evaporation method and laser beam evaporation method, by using an alumina crucible with better heat preservation than a carbon crucible as an evaporation crucible, the calorific value of the evaporation source can be further increased, so it is more preferred.

[0056] <Resin film>

[0057] The resin film 1 used in the present invention is preferably a thin film formed by molding a polymer such as a synthetic resin into a thin film. As the resin film preferably used in the present invention, for example, a polyester film can be exemplified, and among the polyester films, polyethylene terephthalate film, polyethylene naphthalate film, or polyimide film, polyphenylene sulfide film, and polypropylene film are particularly preferred. Among them, polyethylene terephthalate film is more preferably used. These resin films can be used alone or in combination. In addition, a film coated with a resin, an adhesive, etc. on the surface of the resin film can also be used.

[0058] The thickness of the resin film 1 is preferably 1 μm to 20 μm, and more preferably 3 μm to 10 μm. The thickness of the resin film is preferably thinner for the purpose of thinning the electrode substrate, and more preferably 10 μm or less. However, if it is too thin, the yield may be reduced due to breakage in the manufacturing process, so it is more preferably 3 μm or more.

[0059] The surface roughness Ra of the resin film is preferably 0.6 nm or more and 2.0 nm or less. When the surface roughness of the resin film is less than 0.6 nm, when the resin film is wound into a roll, it sometimes sticks and becomes difficult to transport. The surface roughness of the resin film is preferably 0.6 nm or more, and more preferably 1.0 nm or more. On the other hand, since the surface roughness of the aluminum metal film is preferably larger, if the surface roughness Ra of the resin film is increased, it becomes easy to break when the resin film is transported, so it is not preferred. As a resin film, it is preferred to form the minimum unevenness required for transportation and be as smooth as possible, so the surface roughness Ra is preferably 2.0 nm or less, and more preferably 1.5 nm or less.

[0060] <Anchoring layer>

[0061] The metallized film 4 of the present invention may have an anchor layer 2 between the resin film and the aluminum metal film 3. By providing the anchor layer 2, it is expected that the adhesion between the resin film and the aluminum metal film will be improved. As the anchor layer 2, it is preferred to form a metal layer on the resin film by sputtering. In the case of the sputtering method, the thickness of the anchor layer can be made thinner, and it is most suitable for storage battery applications that require thinner films.

[0062] As the anchoring layer 2, it is preferred that the anchoring layer 2 includes one or more metal layers selected from the group consisting of aluminum, nickel, titanium, nickel-chromium alloy, and chromium, and the anchoring layer 2 is further preferably an aluminum metal layer formed by sputtering. At this time, it should be noted that it is important to form a copper layer thereon while maintaining a state in which the surface of the metal such as aluminum, nickel, titanium, chromium, nickel-chromium alloy selected as the anchoring layer 2 is not oxidized. Specifically, after the metal layer is formed as the anchoring layer 2 by sputtering, it is important to form the aluminum metal film 3 while maintaining a vacuum state without opening it to the atmosphere. If the surface of the metal such as aluminum, nickel, titanium, chromium, nickel-chromium alloy selected as the anchoring layer 2 is oxidized, a stable metal oxide film will be formed, and the metal bonding at the interface with the aluminum metal film 3 formed thereon becomes difficult, and the adhesion cannot be ensured, and the aluminum metal film 3 sometimes peels off from the anchoring layer 2. Therefore, it is important not to oxidize the aluminum, nickel, titanium, chromium, nickel-chromium alloy, etc. selected as the anchoring layer 2. When the anchor layer 2 is an aluminum metal layer formed by sputtering, vacuum evaporation of the aluminum metal film 3 thereon allows columnar crystals to grow larger and denser, thereby further suppressing the contact resistance of the aluminum metal film, which is preferred.

[0063] The thickness of the anchor layer 2 is preferably 3 nm to 40 nm, more preferably 5 nm to 20 nm. If the thickness is less than 3 nm, sufficient adhesion may not be obtained. On the other hand, even if the anchor layer is larger than 40 nm, the effect of improving adhesion will not be large, so it is preferably 40 nm or less. In the case of preparing the anchor layer by sputtering method with slow film forming speed, it is further preferred to make the anchor layer 20 nm or less, so as to improve productivity.

[0064] Example

[0065] Hereinafter, the present invention will be described based on examples. It should be noted that the present invention is not limited to these examples, and these examples can be modified and altered based on the gist of the present invention, and these are not excluded from the scope of the invention.

[0066] (Magnetron Sputtering)

[0067] The resin film was placed in a batch vacuum deposition apparatus (EBH-800 manufactured by ULVAC) using a target of 50 mm × 550 mm in size and adjusted to a vacuum degree of 5 × 10 -1 Pa or less, and continuously apply DC power until the metal film thickness reaches a predetermined value.

[0068] Alternatively, a resin film was placed in a roll vacuum deposition apparatus (EWC-060 manufactured by ULVAC) using a target of 70 mm × 550 mm in size, and the vacuum was adjusted to a degree of vacuum of 1 × 10 -2 Pa or less, a pulse power supply is applied to form a metal layer.

[0069] It should be noted that, unless otherwise specified, sputtering and vacuum deposition were performed continuously so that the anchor layer and the aluminum metal film were not in contact with the atmosphere.

[0070] (Vacuum deposition)

[0071] The resin film was placed in a batch vacuum deposition apparatus (EBH-800 manufactured by ULVAC), and aluminum was placed on a deposition boat in an amount to achieve a target thickness. The deposition boat was evacuated to a vacuum degree of 9.0 × 10 -3 Pa or less, and then the deposition boat is heated to perform vacuum deposition to form an aluminum metal film.

[0072] Alternatively, the resin film is placed in a roller vacuum deposition device (EWC-060 manufactured by ULVAC), and the aluminum ingot is heated by an induction heating deposition method using a carbon crucible under conditions where the conveying speed and output are such that the aluminum film thickness reaches a specified value, thereby performing vacuum deposition to form an aluminum metal film.

[0073] Alternatively, the resin film is placed in a roll vacuum deposition apparatus (EWC-060 manufactured by ULVAC), and an aluminum wire is introduced into a deposition boat heated by resistance heating at a conveying speed at which the aluminum film thickness reaches a predetermined value, thereby performing vacuum deposition to form an aluminum metal film.

[0074] (About the introduction of argon gas)

[0075] The argon gas introduced during magnetron sputtering was used for the introduction of the argon gas. In a batch vacuum deposition apparatus (EBH-800 manufactured by ULVAC), sputtering and vacuum deposition were not performed simultaneously, so argon gas was not introduced during vacuum deposition.

[0076] In a roll vacuum deposition apparatus (EWC-060 manufactured by ULVAC), sputtering and vacuum deposition were continuously performed, and therefore sputtering and vacuum deposition were simultaneously performed in the same deposition chamber, and argon gas was always introduced into a deposition source of vacuum deposition.

[0077] (XRD (X-ray diffraction) measurement method)

[0078] The measurement was performed using X-ray diffraction (RIGAKU SmartLab9kW). The measurement conditions were as follows: the voltage and current of the X-ray tube were 45kV-200mA, the scanning speed was 2° / min, the incident slit was 1.0mm, and the receiving slit was 1.0mm. The peak intensity I

[111] of the X-ray diffraction of the 111 plane and the peak intensity I

[200] of the X-ray diffraction of the 200 plane that appeared in the measurement results were determined, and the ratio I

[200] / I

[111] was calculated and compared.

[0079] (Contact resistance measurement)

[0080] On a 10 mm thick NR sponge rubber (NRS-06 manufactured by Waki ​​Sangyo Co., Ltd.), a metalized film was placed with the metal film facing upward, and two 25 mm × 25 mm gold-plated copper plates were separated by 1 mm and a 500 g weight was placed on each copper plate. The resistance value between the two copper plates was measured using a resistance meter RM3544 manufactured by Hioki Electric Co., Ltd. as the contact resistance.

[0081] (Surface resistance measurement)

[0082] The metallized film was cut into a size of about 300 mm x about 80 mm, and the surface resistance at three locations was measured by a four-terminal method using a simple low resistivity meter ("Loresta (registered trademark)" EP MCP-T360 manufactured by Mitsubishi Chemical Analytech Co., Ltd.), and the average value was used as the surface resistance value.

[0083] (Aluminum metal film thickness)

[0084] The metallized film was cut into a size of about 30 mm x about 30 mm, 10 pieces were overlapped, and the thickness was measured with a micrometer to calculate the thickness of the metallized film per piece. Then, the thickness of the aluminum metal film was calculated from the difference between the thickness of the undeposited resin film measured with a micrometer by overlapping 10 pieces in the same way and the thickness of the metallized film.

[0085] (Surface roughness)

[0086] The surface roughness Ra was measured using a scanning white light interference microscope manufactured by Hitachi High-Tech Science Corporation. The measurement conditions were as follows: the measurement mode was "wave", the light source was 530 White (white), the objective lens was 50 times, and the accompanying analysis software was used. The values ​​were calculated under the conditions of surface correction of 4 times, completion of "complete", and Gaussing filter of "cutoff 2 μm".

[0087] (Close fit evaluation)

[0088] A paper tape (NITTO, No. 720) with a width of 18 mm was attached to the surface of the aluminum metal film, and then the evaporation film was judged by whether it could be peeled off from the resin film when the paper tape (NITTO, No. 720) was peeled off. In the case where the evaporation film was peeled off from the resin film, it was evaluated as × (unqualified), and in the case where it was not peeled off, it was evaluated as 0 (qualified), which was used as a standard for whether it could be used as a metallized film for a positive electrode of a secondary battery.

[0089] (Example 1)

[0090] A biaxially oriented polyethylene terephthalate film (SKC Co., Ltd., model: SC42) with a thickness of 11.5 μm was used as the resin film. The surface roughness of the resin film was 1.6 nm. For the roll-shaped blank of the resin film, the resin film was placed in a roller vacuum deposition device (ULVAC EWC-060), a pulse power supply was applied, and aluminum was deposited to a thickness of 5 nm by sputtering. As a condition, a pulse power supply was used and the sputtering output was 2.0 kW. Then, the aluminum ingot was heated by an induction heating deposition method using a carbon crucible, and the aluminum metal film was vacuum deposited to a thickness of 1.48 μm by a vacuum deposition method.

[0091] For the metallized film produced in this way, the ratio of the peak intensity I

[200] of the X-ray diffraction of the 200 plane to the peak intensity I

[111] of the X-ray diffraction of the 111 plane of aluminum, I

[200] / I

[111] , was 4.3, and the surface roughness was 8.3 nm.

[0092] The surface resistance value of the aluminum metal film surface not in contact with the resin film of the metal film was 0.037Ω / □, the contact resistance value was 8.63mΩ, and the ratio of the contact resistance value to the surface resistance value [contact resistance / surface resistance] was 0.24.

[0093] The contact resistance value was 15 mΩ or less, which was sufficiently small and was judged to be acceptable, i.e., 0.

[0094] (Examples 2 to 5)

[0095] A metallized thin film was produced and evaluated in the same manner as in Example 1, except that the thickness of the aluminum metal film was as shown in Table 1. The results are shown in Table 1.

[0096] (Example 6)

[0097] A biaxially oriented polyethylene terephthalate film (SKC Co., Ltd., Model: SC42) with a thickness of 11.5 μm was used as the resin film. The surface roughness of the resin film was 1.6 nm. The roll-shaped raw material of the resin film was placed in a roll vacuum deposition device (ULVAC EWC-060), and the vacuum was adjusted to a degree of 1×10 -2 After the temperature reached Pa or less, an aluminum wire was placed in a deposition boat heated by resistance heating to perform vacuum deposition, and an aluminum metal film was vacuum-deposited to a thickness of 1.04 μm and evaluated.

[0098] (Example 7)

[0099] A biaxially oriented polyethylene terephthalate film (SKC (Strain), model: SC42) with a thickness of 11.5 μm was used as the resin film. The surface roughness of the resin film was 1.6 nm. For the roll-shaped blank of the resin film, the resin film was placed in a roller vacuum deposition device (ULVAC EWC-060), a pulse power supply was applied, and aluminum was deposited to a thickness of 5 nm by sputtering. As a condition, a pulse power supply was used and 2.0 kW was adopted for sputtering output. Then, an aluminum wire was put into a deposition boat heated by resistance heating, and vacuum deposition was performed, and the aluminum metal film was vacuum deposited to a thickness of 1.00 μm and evaluated. The results are shown in Table 1.

[0100] (Comparative Example 1)

[0101] A biaxially oriented polyethylene terephthalate film (SKC (co., Ltd., model: SC42) with a thickness of 11.5 μm was used as the resin film. The surface roughness of the resin film was 1.6 nm. For the resin film, the resin film was placed in a batch vacuum deposition device (EBH-800, ULVAC), a pulse power supply was applied, and aluminum was deposited to a thickness of 5 nm by sputtering. As a condition, a pulse power supply was used and 2.0 kW was used for sputtering output. Then, the aluminum metal film was vacuum deposited to a thickness of 1.44 μm by a resistance heating deposition method in which the deposition boat was heated.

[0102] For the metallized film produced in this way, the ratio of the peak intensity I

[200] of the X-ray diffraction of aluminum at the 200 plane to the peak intensity I

[111] of the X-ray diffraction of aluminum at the 111 plane was 0.3, and the surface roughness was 1.6 nm.

[0103] The surface resistance value of the aluminum metal film surface of the metal film not in contact with the resin film was 0.038Ω / □, the contact resistance value was 15.38mΩ, and the ratio of the contact resistance value to the surface resistance value [contact resistance / surface resistance] was 0.41.

[0104] The contact resistance value was greater than 15 mΩ, which was high relative to the surface resistance and was judged as unacceptable, ie, ×.

[0105] (Comparative Examples 2 to 5)

[0106] A metallized thin film was produced and evaluated in the same manner as in Comparative Example 1, except that the thickness of the aluminum metal film was as shown in Table 1. The results are shown in Table 1.

[0107] [Table 1]

[0108]

[0109] Description of Reference Numerals

[0110] 1. Resin film

[0111] 2 Anchoring layer

[0112] 3 Aluminum metal film

[0113] 4 metallized film

Claims

1. A metallized film for a secondary battery positive electrode, wherein: An aluminum metal film is formed on at least one surface of the resin film. In the metal film, a ratio I[200] / I[111] of a peak intensity I[200] of X-ray diffraction of aluminum at a 200 plane to a peak intensity I[111] of X-ray diffraction of aluminum at a 111 plane is greater than or equal to 1.

0.

2. The metallized film for a secondary battery positive electrode according to claim 1, wherein: The surface resistance of the metal film is 0.15Ω / □ or less.

3. The metallized film for a secondary battery positive electrode according to claim 1 or 2, wherein: The surface roughness Ra of the resin film is greater than or equal to 0.6 nm and less than or equal to 2.0 nm.

4. The metallized film for a secondary battery positive electrode according to claim 1 or 2, wherein: The surface roughness Ra of the metal film is greater than or equal to 2.3 nm and less than or equal to 10.0 nm.

5. A method for producing a metallized film for a secondary battery positive electrode, which is the method for producing a metallized film for a secondary battery positive electrode according to claim 1 or 2, comprising: A step of forming a film by heating aluminum as a deposition source by at least one selected from the group consisting of resistance heating, induction heating, and electron beams and introducing argon gas when the aluminum is vaporized, and vaporizing the vaporized aluminum on a resin thin film.

6. The method for manufacturing a metallized film for a secondary battery positive electrode according to claim 5, comprising: After forming aluminum on the resin thin film by sputtering, a film-forming step is performed by vapor-depositing the vaporized aluminum without exposing the film to the atmosphere.

Citation Information

Patent Citations

  • Film for secondary battery electrode

    JP1998040919A

  • Electric current collector, electrode and electric charge storing device

    JP2008160053A